A Comparison of Spinal Anesthesia Versus Monitored Anesthesia Care With Local Anesthesia in Minimally Invasive Fetal Surgery. Issue 3 (September 2020) - Ferschl, M.B.; Feiner, J.; Vu, L.; Smith, D.; Rollins, M.D.
Abstract : ( Anesth Analg . 2020;130:409–415) The most common minimally invasive fetal surgeries are selective fetoscopic laser photocoagulation to treat twin-to-twin transfusion syndrome and radiofrequency ablation using twin-reversed arterial perfusion sequence. The anesthetic techniques for these surgeries have evolved from general endotracheal anesthesia to spinal anesthesia with or without intravenous sedation in the United States, though in some other countries local anesthesia infiltration is used. This study aimed to compare spinal anesthesia and local anesthesia with or without sedation in these 2 surgeries in terms of safety and efficacy.